Multimodalitas linguistis-visual dalam morfologi bahasa Indonesia: persepsi pemaduan dalam pengembangan desain pembelajaran - Setyaningsih, Yuliana (Universitas Mulawarman, 2023)
This research aims to describe students' perceptions regarding the integration of linguistic-visual multimodality texts in the design of developing Indonesian morphology textbooks. Data were obtained by applying the nonface-to-face interview method through a list of questions to explore opinions and expectations about the need to integrate linguistic-visual multimodality texts in the design of Indonesian morphology textbooks. Data analysis was carried out by applying the equivalent method which includes identification, classification, and interpretation steps. The findings of this research illustrate that students responded positively to the integration of linguistic-visual aspects in the design of developing Indonesian morphology textbooks. The integration of elements such as images, tables, graphs, photos, text, colors, and infographics in textbook design was assessed very positively by respondents.